DAMPAK MOTIVASI KERJA TERHADAP PRODUKTIVITAS DI PT. SEMEN BATURAJA (PERSERO), TBK SITE PANJANG - Riana Septiani; Aryo Wahyudi (Fakultas Teknik Universitas Tulang Bawang Lampung, 2017)
PT. Semen Baturaja (Persero) Tbk, site Panjang is State-Owned Enterprises make to cement industry in Bandar Lampung City. Low productivity in this company, because the company failed to give motivation. The motivation influenced by several factors are administration of company, leadership, salary, employee interaction, and work conditions. From the fifth factors, will be research how much influence to productivity. The research make a questionnaire to employee in department of operation. The result of questionnaire is a qualitative data will be changed to quantitative data by using SPSS program. Based on calculation, the motivation have influence to productivity is 44,80%, and other factors is not researched. From the fifth factors, administration of company and company policy is very influence to productivity. The best solution is give a reward and training to employee, so productivity has to increase. Other factors have influence are leadership, job conditions, salary, and employee interaction.